Body image of tall and medium girls aged 13-17 years Wizerunek ciała wysoko- i normorosłych dziewcząt w wieku 13-17 lat - Joanna Głogowska; Katarzyna Milde; Romuald Stupnicki (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: Adolescent girls often experience difficulties in a rational perception of own body and consider attaining an ?appropriate shape? as a key to success and happiness. Growth disorders, like e.g. very tall stature, may bring about stigmatising which, in turn, may decrease in such girls their self-esteem, especially in adolescence. Aim of the study was to assess the perceived body image of tall and medium-statured girls and to compare their self-rating with an external one. Material and methods: A group of 56 girls aged 13-17 years were classified into two categories of body height: medium stature, between Percentiles 40 and 60 (n=36) and tall, above Percentile 90 (n=20). Using a template containing 9 female body shapes, the girls indicated the shape they thought they had, the shape they wished to have, and an external rating was also made. Girls rated as shapes 1 or 2 were classified as thin, shapes 3 or 4 as medium and shape 5 or higher as robust. The data were related to the BMI values. Results: Thin girls self-rated their body shapes and the desired ones significantly higher (p <0.05) compared with the external rating. In medium-shaped girls the same was true for self-rating, the desired shape being concordant with the external rating. In robust girls, the external and self-ratings were concordant, the desired shapes being significantly lower (p <0.05) but higher (p <0.05) in tall than in medium-height girls (5.0 and 3.9, respectively). Tall and medium girls did not differ significantly in BMI but a very high correlation (r=0.930; p<0.001) was found between the externally rated body shape and BMI in both groups of girls. Conclusion: The distorted perception of own body shape by adolescent girls may result from the specific ideals of feminine beauty and excessively slim silhouette insistently promoted by mass media and fashion designers. Popularisation of the results of this and similar studies may contribute to altering the respective attitudes of adolescent girls.